PENINGKATAN KEMAMPUAN MEMAHAMI IMAN KEPADA ALLAH DENGAN MENGGUNAKAN METODE SMART GAME (TEPUK SIFAT WAJIB DAN MUSTAHIL) DALAM PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH PADA SISWA KELAS VII B SMPN 2 PANTI, KABUPATEN JEMBER - Qibtiyah, Mariyatul (Balai Diklat Keagamaan Surabaya, 2018)
PAI learning is still much centered on the teacher, the source of learning isstill minimal, less supportive learning media, student organization thathas not been optimal and the use of mono methode is the factors thatcause low student learning outcomes. In the learning process of PAI byusing the conventional method on the matter of faith to God there arestill many students who have difficulty in comprehending reasoning androte materials such as mandatory nature, improbability and the natureof the jewels for Allah, it is proven that there are still many students’ scoreare under the KKM, it can be seen from the results Student repeat withaverage score: 6.7. While the value of KKM determined in seventh gradestudents amounted to 75. This study aims to describe the use of smartgame method in cooperative learning type make a match to improve theability to understand the faith to God. This research was conducted atSMPN2 Panti in grade VIIb students having address at Jalan Rajawali 108Kemuningsari Lor Sub Panti Jember Regency. There were two cycles in thisstudy which each cycle was done in 2 (two) meetings. Instruments usedto collect data was observation sheets and test questions. The data wasanalysed by using comparative descriptive analysis. Based on dataanalysis, it is concluded that there is an increase of observation result tostudent’s learning activity, in cycle I the percentage of score is 77 %, is inenough category, and in cycle II the percentage of score increases to91,6 %. In a very good category. Based on observations made by colleagueson teacher activity on the first cycle of the percentage score is 76 % are inenough categories. In cycle II the percentage score increased to 90 %. Thisshows that the level of success of teachers during the learning activitiesare in good category. The results of the assessment in the first cycle therewas an increase in the average value of students from the pre-cycle 67,increased in the first cycle to 72. But this average value was still belowKKM 75. Then the results of cycle II value increased to 83.26 this value hasbeen Reaching KKM and learning completeness. From the results ofinterviews on students by applying the Smart Game method in the Cooperative Learning model of Make A Match type students feel happyin learning. Suggested for teachers by using the method is expectedto foster the spirit in learning PAI, especially in memorizing the natureof mandatory and impossible.